ASSESSMENT OF TRANSPORT PROJECT (Perner's Contacts, 2009)
This paper deals with assessment of particular variants of road and railway infrastructure building. Assessment results from economical and financial analysis and from total rate of social value in terms of transportation efficiency and safety.
Keywords: road infrastructure; railway infrastructure